Local contributions to beta diversity in urban pond networks: Implications for biodiversity conservation and management. Issue 5 (15th March 2021) - Hill, Matthew J.; White, James C.; Biggs, Jeremy; Briers, Robert A.; Gledhill, David; Ledger, Mark E.; Thornhill, Ian; Wood, Paul J.; Hassall, Chris
Abstract: Aim: An understanding of how biotic communities are spatially organized is necessary to identify and prioritize habitats within landscape‐scale biodiversity conservation. Local contribution to beta diversity (LCBD) identifies individual habitats that make a significant contribution to beta diversity and may have important practical implications, particularly for conservation of habitat networks. In this study, we develop and apply a conservation prioritization approach based on LCBD in aquatic invertebrate communities from 132 ponds. Location: Five urban settlements in the UK: Halton, Loughborough, Stockport, Birmingham and Huddersfield. Methods: We partition LCBD into richness difference (nestedness: RichDiff LCBD) and species replacement (turnover: Repl LCBD) and identify key environmental variables driving LCBD. We examine LCBD at two scales relevant to conservation planning: within urban settlements and nationally across the UK. Results: Significant differences in LCBD values were recorded among the five settlements. In four of the five urban settlements studied, pond sites with the greatest LCBD values typically showed high replacement values. Significant LCBD sites and sites with high taxonomic diversity together supported more of the regional species pool (70%–97%) than sites with high taxonomic diversity alone (54%–94%) or what could be protected by the random selection of sites. LCBD was significantly associated with vegetation shading, surface area, altitude and macrophyte cover. Main conclusions: Conservation prioritization that incorporates LCBD and sites with high taxonomic diversity improves the effectiveness of conservation actions within pond habitat networks, ensures sites supporting high biodiversity are protected and provides a method to define a spatial network of protected sites. Identifying new, effective conservation approaches, particularly in urban areas where resources may be scarce and conflicts regarding land use exist, is essential to ensure biodiversity is fully supported, and detrimental anthropogenic effects are reduced.